Synthesis, Spectroscopy and Biological Activity Study of Some New Complexes with Schiff Base Derived From Malonic Acid Dihydrazide with 2-pyridine Crboxaldehyde (Baghdad Science Journal, 2024)
From synthesized novel ligand (L) made of Malonic acid dihydrazide and 2-pyridine carboxaldehyde, new complexes have been created. Ni(II), Cu(II), and Zn(II) complexes were created as a result. FT-IR, UV-Vis, Mass, 1H-NMR, 13C-NMR, C.H.N., Chloride-containing, Molar Conductance, Magnetic Susceptibility, and Atomic Absorption have all been used to identify these compounds. For each Nickel, Copper, and Zinc complexes the characterization findings revealed complexes with hexadentate octahedral coordination geometry and tetradentate ligand. Two Gram-positive (Staphylococcus aureus and Bacillus subtitles) and two Gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacteria, as well as candida fungus, were evaluated for the biological activities of the novel compounds. With the exception of the Nickel complex, which failed to produce any effective inhibitory effects against pseudomonas, their results in inhibition were good.